2012
DOI: 10.1182/blood-2012-01-404368
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study results of the type II glycoengineered humanized anti-CD20 monoclonal antibody obinutuzumab (GA101) in B-cell lymphoma patients

Abstract: Whereas the chimeric type I anti-CD20 Ab rituximab has improved outcomes for patients with B-cell malignancies significantly, many patients with non-Hodgkin lymphoma (NHL) remain incurable. Obinutuzumab (GA101) is a glycoengineered, humanized anti-CD20 type II Ab that has demonstrated superior activity against type I Abs in vitro and in preclinical studies. In the present study, we evaluated the safety, efficacy, and pharmacokinetics of GA101 in a phase 1 study of 21 patients with heavily pretreated, relapsed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
150
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(152 citation statements)
references
References 21 publications
2
150
0
Order By: Relevance
“…Two prime examples of successful therapeutic development leveraging the effects of protein glycosylation are the development of a long-acting erythropoietin (darbepoetin alfa; Aranesp; Amgen) with increased sialylation content, which reduces the clearance facilitated by the asialoglycoprotein receptor (37), and the development of an anti-CD20 antibody (obinutuzumab; GAZYVA; Genentech) that is devoid of Fc fucosylation, which has enhanced effector function and antitumor properties (38). Identification of the important role of terminal sialic acid-containing IgG glycoforms for IVIg activity in 2006 (23) and its confirmation by several independent laboratories in the past few years .…”
Section: Discussionmentioning
confidence: 99%
“…Two prime examples of successful therapeutic development leveraging the effects of protein glycosylation are the development of a long-acting erythropoietin (darbepoetin alfa; Aranesp; Amgen) with increased sialylation content, which reduces the clearance facilitated by the asialoglycoprotein receptor (37), and the development of an anti-CD20 antibody (obinutuzumab; GAZYVA; Genentech) that is devoid of Fc fucosylation, which has enhanced effector function and antitumor properties (38). Identification of the important role of terminal sialic acid-containing IgG glycoforms for IVIg activity in 2006 (23) and its confirmation by several independent laboratories in the past few years .…”
Section: Discussionmentioning
confidence: 99%
“…given for 4 decreased after subsequent infusions because of a reduction in the available target antigen. 54,57 Absorption. After i.v.…”
Section: -34mentioning
confidence: 99%
“…In line with these properties, a number of preclinical studies demonstrated that Ab Fcafucosylation translates into significantly enhanced activity in vivo (6,9,17), and this has led to the approval of new therapeutic GE Abs. GA101 (obinutuzumab) is a GE, type II anti-CD20 mAb that has recently been approved by the U.S. Food and Drug Administration for the first line treatment of patients with chronic lymphocytic leukemia (CLL) in combination with chlorambucil (18)(19)(20). In Japan, the GE CCR4 Ab mogamulizumab has been approved for treatment of patients with relapsed or refractory CCR4 + T cell leukemia-lymphoma (21).…”
mentioning
confidence: 99%